Keefektifan Flashcards pada Web Pembelajaran Memory untuk Meningkatkan Kemampuan Kosakata Bahasa Jepang - Lathiifah Triana Dewi; Ai Sumirah Setiawati; Rina Supriatnaningsih; Andy Moorad Oesman (Chi'e: Journal of Japanese Learning and Teaching, 2022)
The study aimed to test the effectiveness of flashcards on the Memory learning web on improving students' Japanese vocabulary skills and students' responses to media. This research uses True Experimental Design with Posttest–Only Control Group Design. Data collection techniques using test methods and questionnaires. The data analysis technique used the Mann Whitney–U formula. The calculation results obtained an average value of 80.53 in the experimental group and 70.05 in the control group. The results of the Mann Whitney–U test were obtained by Asymp. Sig. (2–tailed) 0.031 < 0.05, indicating that the average score of the experimental group and control group students had a significant difference. It can be concluded that flashcards on the verified Memory learning web effectively increase students' Japanese vocabulary. Then from the questionnaire data, it can be seen that Memory has interesting multimedia features. However, the effectiveness of Memory has not given optimal effect. This is known from the difference in the score interval on the posttest results, which is too obvious, namely 93. The inequality is related to the independence and intensity of students using Memory which is still rare.